2016
DOI: 10.1177/0021955x16652101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azodicarbonamide on microstructure, cure kinetics and physical properties of natural rubber foam

Abstract: The effect of azodicarbonamide as chemical blowing agent on the morphology, cure kinetics and physical properties of natural rubber foam is investigated. From the morphology, when the amount of chemical blowing agent increases from 3 to 4 phr, the bubble size in the rubber matrix slightly decreases due to the increase of vulcanization reaction rate from the presence of amine fragment species as by-products from the decomposition of azodicarbonamide. The coalescence between bubbles is observed in the specimen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Cure characteristics of the natural rubber compound were observed by rheograph from a MDR at 155°C, which was a temperature used for curing the rubber compound by compression molding process. Cure characteristics are the important factors for controlling the bubble size and microvoid structure in the rubber foam system affecting the mechanical and thermal properties of NRF . As displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cure characteristics of the natural rubber compound were observed by rheograph from a MDR at 155°C, which was a temperature used for curing the rubber compound by compression molding process. Cure characteristics are the important factors for controlling the bubble size and microvoid structure in the rubber foam system affecting the mechanical and thermal properties of NRF . As displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although NRF/CG3 showed the highest tensile strength, it revealed slightly higher compression set than NRF/UG3 due to the slightly larger bubble size resulting in poor distributive force in the rubber foam system. It might be concluded from this finding and our previous work that the optimal mechanical properties of natural rubber nanocomposite foam will be acquired for the uniformly distributed small bubble size in natural rubber matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mold was opened and the prepared foams were kept at room temperature for 24 hours. For conventional foams, a two‐step unlimited‐expansion foaming method as a standard procedure was used . The compounds were preheated and precured in a hot press (120°C, 10 minutes) and then placed in a hot air oven (160°C, 30 minutes) for simultaneously curing and foaming.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of foaming agent content on the morphology and properties of NR foams was studied by Najib et al for sodium bicarbonate and by Charoeythornkhajhornchai et al for azodicarbonamide (ADC). It was reported that foam density, mechanical properties (modulus and hardness), and curing properties (cure content and ultimate torque) were all decreasing with increasing foaming agent content.…”
Section: Introductionmentioning
confidence: 99%